Experimental investigation and constitutive modeling of randomly oriented electrospun nanofibrous membranes / Wong Dannee - Wong, Dannee (2018)
The recent advancement of nanotechnology has enabled the fabrication of nanofibers through a number of processing techniques. Among these, electrospinning offers a unique ability to produce nanofibrous membranes for different materials and of different assemblies or textures that make them suitable for various applications including filtration, tissue engineering, nanocomposites and textiles. In these applications, electrospun nanofibrous membranes are frequently subjected to complex stresses and strains which could lead to fiber failures. Therefore, the understanding of their mechanical properties becomes crucial in order to facilitate the design and performance evaluation of the materials. In view of probing the mechanical response of nanofibrous membranes, relevant experimental characterizations are conducted such as atomic force microscopy (AFM), nanoindentation, nanotensile tests or conventional tensile tests. These experimental techniques are often daunting, costly and time-consuming. If a robust and cost-effective alternative method in evaluating the mechanical properties of electrospun nanofibrous materials through numerical simulation can be established, the strong dependence on experimental works can therefore be significantly reduced. The present thesis focuses on the development of a simple constitutive model with reduced number of material parameters for the mechanical response of randomly oriented electrospun PVDF nanofibrous membranes. To this end, the thesis is divided into two parts. The first part focuses on the experimental aspects that include the fabrication of electrospun nanofibrous membranes using different sets of electrospinning parameters and the characterization of their surface morphology. Subsequently, samples obtained using the optimum set of parameters are chosen for further characterizations, i.e. physical evaluation of undeformed and deformed membranes, mechanical testing and fiber orientation analysis. Three types of uniaxial mechanical tests are conducted: monotonic tensile tests, cyclic loading tests with increasing maximum strain and cyclic-relaxation tests. Results show that the material exhibits complex mechanical responses, which include finite strain, irreversible deformation, hysteresis and time-dependent response. Furthermore, fiber orientation analysis suggests that the material is initially isotropic in the plane (transversely isotropic) and the deformation-induced fiber re-orientation takes place. The second part of the thesis deals with the development of a constitutive model capturing the observed responses. Motivated by the experimental observation, the model development starts from the description of material response at fiber-scale in order to describe individual fiber response and irreversible inter-fiber interactions using hyperelastic and large strain elasto-plastic frameworks respectively. The macroscopic response of the membranes is subsequently obtained by integrating the fiber responses in all possible fiber orientations. The efficiency of the proposed model is assessed using experimental data. It is found that the model is qualitatively in good agreement with uniaxial monotonic and cyclic tensile loading tests. Two other deformation modes, i.e. equibiaxial extension and pure shear (planar extension) are simulated to further evaluate the model responses.